2016
DOI: 10.1007/s11274-016-2069-5
|View full text |Cite
|
Sign up to set email alerts
|

Cloning of the cnr operon into a strain of Bacillaceae bacterium for the development of a suitable biosorbent

Abstract: In this study, a potential microbial biosorbent was engineered to improve its capacity to remediate heavy metal contaminated water resources. A Bacillaceae bacterium isolated from a mining area was transformed with a plasmid carrying the (pECD312)-based cnr operon that encodes nickel and cobalt resistance. The bioadsorption ability of the transformed strain was evaluated for removal of nickel from metallurgical water relative to the wildtype strain. Results showed that transformation improved the adsorption ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 47 publications
1
8
0
Order By: Relevance
“…The constant values for the models were calculated as k 1 = 0.025794 and k 2 =0.003064 for the pseudo first and second order kinetic model respectively. The relative fitness of the pseudo second order kinetic model to the adsorption data also shows that the adsorption of sulphate by the polyampholyte occurs through a combination of physical and chemical mechanisms as expected [24][25][26][27][28][29][30][31][32][33][34][35][36]. Good sulphate extraction capacities are observed and can be seen in Fig.…”
Section: Eds Analysissupporting
confidence: 57%
“…The constant values for the models were calculated as k 1 = 0.025794 and k 2 =0.003064 for the pseudo first and second order kinetic model respectively. The relative fitness of the pseudo second order kinetic model to the adsorption data also shows that the adsorption of sulphate by the polyampholyte occurs through a combination of physical and chemical mechanisms as expected [24][25][26][27][28][29][30][31][32][33][34][35][36]. Good sulphate extraction capacities are observed and can be seen in Fig.…”
Section: Eds Analysissupporting
confidence: 57%
“…The pseudo-second-order was found to be the better fit, seeing that the coefficient of determination was closer to unity. This indicates that the surface adsorption involving chemisorption, is the rate-limiting step [26][27][28][29][30][31][32][33][34][35][36][37]. This result therefore indicates that there is a stronger interaction between the surface of the clinoptilolite and the zinc ions.…”
Section: Fig 3: Freundlich Plotmentioning
confidence: 83%
“…To validate the Langmuir and Frendlich isotherm models, the adsorption data at various initial Cd concentrations were considered and the isotherm parameters determined by plotting C e /q e vs C e and log q e vs log C e , respectively. The constants achieved from this process are shown in Table 1: From Table 1 it can be observed that the coefficient of determination (R 2 ) in all cases is close to unity, therefore, the Langmuir and the Freundlich isotherm models fit the adsorption equilibrium data for the adsorption of cadmium by both the the treated and untreated biochars, implying that cadmium binds to groups at the surface and in the pores of adsorbents (homogeneous and heterogeneous surface) [26][27][28][29][30][31][32][33][34][35].…”
Section: Varying Initial Concentration Experimentsmentioning
confidence: 90%